Discovery of a Chiral DNA‐Targeted Platinum–Acridine Agent with Potent Enantioselective Anticancer Activity. (29th September 2020) - Zhang, Shenjie; Yao, Xiyuan; Watkins, Noah H.; Rose, P. Keegan; Caruso, Sofia R.; Day, Cynthia S.; Bierbach, Ulrich
Abstract: A structure–activity relationship study was performed for a set of rigidified platinum–acridine anticancer agents containing linkers derived from chiral pyrrolidine and piperidine scaffolds. Screening a library of microscale reactions and selected resynthesized compounds in non‐small‐cell lung cancer (NSCLC) cells showed that cytotoxicities varied by more than three orders of magnitude. A potent hit compound was discovered containing a (R)‐N‐(piperidin‐3‐yl) linker (P2‐6R ), which killed NCI‐H460 and A549 lung cancer cells 100 times more effectively than the S enantiomer (P2‐6S ). P2‐6R accumulated in A549 cells significantly faster and produced 50‐fold higher DNA adduct levels than P2‐6S . Ligand similarity analysis suggests that only module 6R may be compatible with strainless monofunctional intercalative binding. NCI‐60 screening and COMPARE analysis highlights the spectrum of activity and potential utility of P2‐6R for treating NSCLC and other solid tumors. Abstract : Modular library screening identified a case of highly enantioselective anticancer activity in rigidified, DNA‐targeted platinum–acridine agents. A hit compound, P2‐6R, was identified that shows high potency in chemoresistant cancers and an activity profile across 60 cancer cell lines (NCI‐60) complementary to that of cisplatin and other clinically relevant platinum‐based drugs.